Secret seven adventure - Blyton, Enid. (b, 2004)
The Secret Seven are Peter and his sister Janet, Jack, Colin, George, Pam and Barbara. They meet every holiday in the shed at the bottom of Peter and Janet's garden - and solve mysteries, and eat lots of delicious food. But no one can enter the shed without whispering the secret password! There are 15 Secret Seven novels, and a collection of short stories. When a priceless pearl necklace goes missing, the Secret Seven are the first off the mark to catch the thief. After all, they saw him escape. But will they be able to find the stolen necklace? Each book features rarely seen bonus Blyton: extra stories, a quiz, additional artwork and insights into Blyton's life and writing process.
Keywords: Secret Seven (Fictitious characters) -- Juvenile fiction; Mystery fiction; Secret Seven (Fictitious characters)